Viktimologi Dalam Kasus Kekerasan Berbasis Gender Online Di Indonesia - Amanda Putri; Sania Ulfatun Nikmah; Naura Putri Ramadhania; Ria Anggraeni Utami (GLOBAL SCIENTS PUBLISHER, 2026)
The development of digital technology has given rise to new forms of crime, one of which is online gender-based violence (OGBV), which is increasingly prevalent in Indonesia. This phenomenon demonstrates high vulnerability, particularly for women, as victims in the digital space. This study aims to analyze OGBV from a victimological perspective by highlighting the forms and characteristics of the crime, the vulnerability factors of victims, and available legal protections. The research method used is normative legal research with a legislative and conceptual approach, utilizing secondary data obtained through literature review. The results indicate that OGBV has specific characteristics, such as anonymity, easy spread, and long-term impacts due to digital traces that are difficult to erase. From a victimological perspective, victims experience not only material losses but also serious psychological and social impacts, exacerbated by the phenomena of victim blaming and revictimization. Although Indonesia has regulations in place, the implementation of legal protection for victims of OGBV remains suboptimal. Therefore, a more comprehensive and victim-oriented approach is needed to achieve effective legal protection and justice for victims in the digital era.